The Tourism Students’ Awareness of Communicative Competence in an English as a Foreign Language Context - Anchondo, Ercilia Loera (European Scientific Journal, ESJ, 2018)
The present research aimed to find out the students’ awareness towards the concept of communicative competence and to discover if exposure serves as a tool in the development of the latter. Applying a mixed-method research design, quantitative and qualitative data were gathered with three different instruments: a face-to-face questionnaire, a semi-structured interview, and a structured observation. The subjects consisted of forty-six English as a Foreign Language learners in the intermediate and advanced levels in the Tourism major at the Universidad Autónoma de Ciudad Juárez. Eleven questions were designed to find out the students’ awareness on communicative competence and its components. The interview was based on the elements of communicative competence and the activities related to exposure to the target language. The observation considered details in regards to the students’ performance in the linguistic and pragmatic components of communicative competence. Results indicated that participants are aware of the concept under study and its components. Their answers to the interview and their performance in the observation proposed that exposure to the target language have been used towards the development of certain elements in their communicative competence. Recommendations derived from the present study include making students comprehend what the acquisition of a communicative competence encompasses, which is to manage the target language through the use of the four skills. Secondly, it is of great importance to promote in students the habit of practicing the target language outside the classroom. Finally, it is necessary to pay attention to phonological features such as word stress, pitch, and intonation to improve pronunciation.